Linking Social Support and Performance in Higher Education - Putra, Firdaus; Asbari, Masduki; Purwanto, Agus; Novitasari, Dewiana; Santoso, Priyono Budi (International Journal of Social and Management Studies, 2021)
This study aims to measure the effect of social support factors (supervisor, peer, and family support) on lecturer performance in a private university in Indonesia. Data collection was carried out by simple random sampling to 172 university lecturer populations. The results of the questionnaire were valid and returned as many as 112 samples. Data processing using SEM method with SmartPLS 3.0 software. The results of this study concluded that all social support factors consisting of supervisor support, peer support, and family support had a positive and significant effect on performance. While the support supervisor has no significant effect on the performance of lecturers. This new research proposes a model for building performance among private university lecturers in Indonesia through increasing social support for lecturer employment.